2005
DOI: 10.1016/j.ejheart.2004.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Serum markers of angiogenesis and myocardial ultrasonic tissue characterization in patients with dilated cardiomyopathy

Abstract: Background and aims: It has been proven that a disturbance in angiogenesis contributes to the progression of myocardial interstitial fibrosis in idiopathic dilated cardiomyopathy (DCM). This study was designed to evaluate the relationship between serum activity of angiogenic factors and myocardial ultrasonic tissue characterization in patients with DCM. Methods and results:We studied 30 patients with DCM and 15 healthy control subjects. Serum levels of vascular endothelial growth factor (VEGF), interleukin (IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…However, our results support the previous findings of Ohtsuka et al They observed that serum IL-13 levels are elevated in DCM and are correlated with echocardiographic left ventricular end diastolic dimension and tissue fibrosis characterized by ultrasound with integrated backscatter. 27 Since integrated back-scatter analysis has a higher ability to assess myocardial fibrosis and myocardial contractility, and it is considered to be correlated with histological findings of myocardial fibrosis in biopsy specimens from patients with DCM, they suggested that serum IL-13 might reflect disease severity in DCM. [28][29][30] Although IL-13 is elevated in patients with heart failure, the source of serum IL-13 has been remained obscure.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results support the previous findings of Ohtsuka et al They observed that serum IL-13 levels are elevated in DCM and are correlated with echocardiographic left ventricular end diastolic dimension and tissue fibrosis characterized by ultrasound with integrated backscatter. 27 Since integrated back-scatter analysis has a higher ability to assess myocardial fibrosis and myocardial contractility, and it is considered to be correlated with histological findings of myocardial fibrosis in biopsy specimens from patients with DCM, they suggested that serum IL-13 might reflect disease severity in DCM. [28][29][30] Although IL-13 is elevated in patients with heart failure, the source of serum IL-13 has been remained obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, increased cardiac VEGF-A expression has been observed in patients with ischemic cardiomyopathy (6,7). Moreover, serum VEGF-A levels are significantly increased in patients with dilated cardiomyopathy (8). VEGF-A is a major proangiogenic factor that is upregulated in response to hypoxia to improve tissue vascularization and is critically involved in physiologic and pathologic blood vessel formation (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Plasma IL-13 levels were increased in chronical heart failure patients including ischemic heart disease, valvular heart disease, dilated cardiomyopathy and hypertrophic cardiomyopathy (Nishimura et al, 2007). Moreover, elevated serum IL-13 level in patient with dilated cardiomyopathy is correlated with electrocardiographic left ventricular end diastolic dimension and tissue fibrosis (Ohtsuka et al, 2005). In contrast, serum IL-13 level is reduced in patients with acute myocardial infarction (Jafarzadeh et al, 2009).…”
Section: Interleukin-13 In Normal and Failing Heartmentioning
confidence: 95%